Exploring b → cτν mediated baryonic decay modes in SMEFT framework - Panda Dhiren; Mohanta Rukmani (EPJ Web of Conferences)
Motivated by the interplay between the LEFT and SMEFT operators at the electroweak scale, we study the interrelation among the B decays mediated by b → cℓνℓ, b → sνℓνℓ and b → sℓℓ (ℓ = e, µ, τ) quark level transitions in the context of six-dimensional SMEFT operators such as Qℓq(3),Qℓedq,Qℓequ(1),Qℓequ(3),andQϕq(3)$${Q_{\ell q}^{(3)},\,{Q_{\ell edq}},\,Q_{\ell equ}^{(1)},\,Q_{\ell equ}^{(3)},\,{\rm{and}}\,Q_{φ q}^{(3)}} $$. We constrain the new physics parameter space through a com-ℓequ ϕq prehensive global fit incorporating the observables RD, RD∗, Pτ(D∗), FL(D∗), RΛ, B(B0 → K∗νν), B(B → K+νν), B(B → K+τ+τ−) and B(Bs → τ+τ−). We then investigate the sensitivity of new physics in the semi-leptonic decay modes of b-baryons, specifically Ξb → Ξcτ− ν¯τ. We further explore the impact of the new physics couplings on several observables such as the differential branching ratio (DBR), forward-backward asymmetry (AFBτ$${A_{FB}^τ} $$) the lepton flavor non-universality (RΞb$${R_{{Ξ _b}}} $$) for this processes.